Implementasi Smart Inkubator Telur Bebek Otomatis Berbasis Solar Cell dan IoT Guna Meningkatkan Profitabilitas Pada UD Putra Jember - Sebastian Verdian Ximenes; Erlanda Miko Prasetya; Akhmad Ja'far Maulana; Amirul Khoiri; Elma Khoiril Laili; Mochamad Irwan Nari (Journal of Community Development, 2025)
Duck farming in Indonesia offers great potential due to its high productivity. One of the duck breeders UD Putra Jember in Kalimalang Hamlet, Jember Regency faces productivity constraints due to using manual hatching equipment monitoring and low profitability. The application of Smart Automatic Egg Hatching Incubator based on Solar Cell and Internet of Things (IoT) aims to increase partner profitability and remotely monitor temperature and humidity in real time in one hatching period for 28 days with a capacity of 750 eggs. The method used in this activity includes several stages such as team coordination with partners, planning and making tools, assistance in using tools and evaluation. The results achieved by partners were an increase in profit of 30.56% or Rp.718,500. This application activity is expected to help the economy of duck farmers in Indonesia.